2020
DOI: 10.1117/1.jbo.25.1.014515
|View full text |Cite
|
Sign up to set email alerts
|

Translation of two-photon microscopy to the clinic: multimodal multiphoton CARS tomography of in vivo human skin

Abstract: Two-photon microscopes have been successfully translated into clinical imaging tools to obtain high-resolution optical biopsies for in vivo histology. We report on clinical multiphoton coherent anti-Stokes Raman spectroscopy (CARS) tomography based on two tunable ultrashort near-infrared laser beams for label-free in vivo multimodal skin imaging. The multiphoton biopsies were obtained with the compact tomograph "MPTflex-CARS" using a photonic crystal fiber, an optomechanical articulated arm, and a four-detecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 37 publications
(49 reference statements)
1
40
0
Order By: Relevance
“…Namely, mitochondria accumulate around the cell's nucleus in the outermost cell layers of AD patients. This has been previously associated with cell inflammation 14,15 . A decrease in the mean AF lifetime and an increase in a a / 1 2 of stratum granulosum cells, without statistical significance, was also observed, indicating decreased metabolic activity 16 .…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Namely, mitochondria accumulate around the cell's nucleus in the outermost cell layers of AD patients. This has been previously associated with cell inflammation 14,15 . A decrease in the mean AF lifetime and an increase in a a / 1 2 of stratum granulosum cells, without statistical significance, was also observed, indicating decreased metabolic activity 16 .…”
Section: Discussionmentioning
confidence: 80%
“…In addition, due to the role NAD(P)H in the cell's metabolic activity, the metabolism can be simultaneously evaluated. It has been previously shown that it can be used to detect inflammation in AD patients [13][14][15][16] . Nevertheless, the analysis is still time-consuming and operator dependent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations